2020
DOI: 10.1097/md.0000000000019652
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of serum thyroglobulin measured at different time points for prognostic evaluation in differentiated thyroid carcinoma patients

Abstract: Although serum thyroglobulin (Tg) is a reliable differentiated thyroid carcinoma (DTC) prognostic marker, its cutoff values can be affected by TSH stimulation status. Serum Tg prognostic values measured at different time points before and after radioactive iodine (RAI) therapy prepared with recombinant human TSH (rhTSH) in DTC patients, were investigated. This study included 160 DTC patients who underwent surgery followed by rhTSH-aided RAI therapy. Their serum Tg levels were measured 7 days before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Some studies demonstrated that Tg measurement after rhTSH stimulation and therapeutic RAI application is of prognostic significance [ 9 , 11 , 13 , 22 ]. Melo et al [ 11 ] reported the prognostic value of Tg5 (i.e., measurement 5 days after first rhTSH injection) in predicting disease status 1 year post-ablation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies demonstrated that Tg measurement after rhTSH stimulation and therapeutic RAI application is of prognostic significance [ 9 , 11 , 13 , 22 ]. Melo et al [ 11 ] reported the prognostic value of Tg5 (i.e., measurement 5 days after first rhTSH injection) in predicting disease status 1 year post-ablation.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between the above-mentioned cutoff values of Tg5 was explained by the presence or absence of prophylactic neck dissection and by surgeon experience in total thyroidectomy. Also recently, Mutstudy et al [ 13 ] showed that Tg levels measured two days after RAI therapy have prognostic significance. ROC curve analysis showed an optimal Tg cutoff value of 3.7 ng/mL, which was confirmed as an independent prognostic factor in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Radioactive iodine resistant (RAIR) cases with metastatic disease are analyzed according to thyroglobulin and TSH change speed in the manuscript by Meng et al. Although the concept has been raised in previous reports and is considered by some authors as an important criterion to determine radioactive iodine-resistant malignancies ( 5 ), they construct a nomogram based on Thyroglobulin stimulated (Ts) differences at ablation and first recurrence: Ts1-Ts2: ΔTgs, as well as Thyroid Stimulant Hormone levels at same periods: TSHs1-TSH2= ΔTSHs. A ratio ΔTgs/ΔTSHs considering these two differences ≤1.5 as well as older age predicts rapid progression of the disease for these patients, which makes closer monitoring imperative, along with considering early administration of TKI agents.…”
mentioning
confidence: 99%